A Novel Technique for Intraoperative Localization of Colonic Tumors during Laparoscopic Colectomy: A Case Report and Review of the Literature - Sanatan Bhandarkar (World Journal of Colorectal Surgery)
When laparoscopic surgery is selected for gastrointestinal resection, accurate tumor localization is important. We used a C-arm intraoperatively in a case where preoperative endoscopic clipping was done at the tumor site. Our patient was an 82-year-old man with moderately differentiated adenocarcinoma in the sigmoid colon. ResolutionTM Clips were applied adjacent to the lesion on the proximal and distal ends. Intraoperatively, the growth over the sigmoid colon was traced using the assistance of the C-arm according to the endoclips placed during colonoscopy. Bipolar current was used to mark the edges of resection based on the C-arm findings. The operative time was 110 minutes. On postoperative day 5, the patient was discharged from the hospital after an uneventful postoperative stay. The combination of preoperative endoscopic clipping and intraoperative C-arm assistance can achieve accurate localization of tumors for laparoscopic surgery, potentially reducing operative time, leading to resection with oncologically safe margins of the colon.